PEMANFAATAN BAHAN ALAM UNTUK MENINGKATKAN PEMAHAMAN LAMBANG BILANGAN PADA ANAK - Siti Mufidah; Elly Purwanti (AZZAHRA, 2020)
This type of research is a classroom action research (PTK). RA students as the research subject. Baitur Rohman Pasir Sakti for children aged 4-5 years with 28 children. Data collection techniques are tests and documentation. The data analysis used is qualitative analysis and quantitative analysis. The analysis was carried out since the first pre-cycle and after giving action in each cycle that had been carried out. Based on the results of the research conducted, it shows that the learning method of natural materials media is in an effort to increase number symbols in children aged 4-5 years RA. Baitur Rohman Pasir Sakti is proven by an increase in learning outcomes by an average of 47.1% in the first cycle to 57.2% in the second cycle, with an increased percentage of learning outcomes, namely 81.25% of the number of 23 children. with the results of applying natural media, it can improve children's learning outcomes. The results of some of the research stated above indicate that the learning method with the application of the natural material method can improve children's learning outcomes in the use of natural material media in an effort to increase number symbols in children aged 4-5 years RA. Baitur Rohman Pasir Sakti, East Lampung.